2021
DOI: 10.1073/pnas.2023738118
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating symbiosis and immunity signals by receptor competition in rice

Abstract: Plants encounter various microbes in nature and must respond appropriately to symbiotic or pathogenic ones. In rice, the receptor-like kinase OsCERK1 is involved in recognizing both symbiotic and immune signals. However, how these opposing signals are discerned via OsCERK1 remains unknown. Here, we found that receptor competition enables the discrimination of symbiosis and immunity signals in rice. On the one hand, the symbiotic receptor OsMYR1 and its short-length chitooligosaccharide ligand inhibit complex f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 47 publications
(69 reference statements)
2
90
0
Order By: Relevance
“…For example, lipochitooligosaccharide Nod Factors are perceived by legumes (Radutoiu et al, 2003;Bozsoki et al, 2020). In rice, shortchained chitotetraose triggers symbiotic signal transduction with the symbiotic complex receptor MYR1-CERK1, and this suppresses the formation of the CEBiP-CERK1 heteromer (Chiu and Paszkowski, 2021;Zhang et al, 2021). Besides, symbionts are also capable of colonizing hosts while overcoming the response to damage-associated molecular patterns (DAMPs) and MAMPs, while a response against pathogens is possible in the presence of non-pathogenic microbes (Zhou et al, 2020).…”
Section: Recognition Phasementioning
confidence: 99%
“…For example, lipochitooligosaccharide Nod Factors are perceived by legumes (Radutoiu et al, 2003;Bozsoki et al, 2020). In rice, shortchained chitotetraose triggers symbiotic signal transduction with the symbiotic complex receptor MYR1-CERK1, and this suppresses the formation of the CEBiP-CERK1 heteromer (Chiu and Paszkowski, 2021;Zhang et al, 2021). Besides, symbionts are also capable of colonizing hosts while overcoming the response to damage-associated molecular patterns (DAMPs) and MAMPs, while a response against pathogens is possible in the presence of non-pathogenic microbes (Zhou et al, 2020).…”
Section: Recognition Phasementioning
confidence: 99%
“…Then, a LysM receptor heteromer OsMYR1/OsLYK2 and OsCERK1 in rice plants recognized the Myc factors secreted by mycorrhiza. However, a recent study by Zhang et al [83] reported that CO4 and its receptor OsMYR1 were not only involved in initiating symbiotic signalling but also involved in reducing rice immunity by decreasing immune signalling induced by CO8, a bioactive immunity signal secreted by mycorrhiza. This study further indicates that a balanced perception of multiple symbiotic receptors in rice is important for the establishment of a successful mutualistic rice plant association with microbes (including Pantoea).…”
Section: Receptors and Signalling Pathways For Recognition Of Microbes In Rice Plantsmentioning
confidence: 99%
“…In plants, innate immune systems can prevent most pathogens, while allowing colonization of symbiosis and beneficial microbes (Bozsoki et al, 2020;Zhou et al, 2020;Fröschel et al, 2021;Zhang et al, 2021). For example, after inoculation with the vascular pathogen Verticillium longisporum, pathogenic oomycete Phytophthora parasitica, or mutualistic endophyte Serendipita indica, plant root cell-layer responses were different, as revealed by cell-layer translatomes analysis, reflecting the fundamentally different colonization strategies of these microbes (Fröschel et al, 2021).…”
Section: Balance Between Plant Immunity and Distinction Of Pathogens From The Rhizosphere Microbiomementioning
confidence: 99%
“…Though the protein structures of CERK6 and NFR1 are very similar, plants use regions II and IV of LysM1 to specifically recognize pathogens (chitin) or symbiotic signaling molecules (Nod factor) and initiate differential signaling of immunity or root nodule symbiosis (Bozsoki et al, 2020). Another recent advance revealed that the CO4 (Chitotetraose) symbiotic receptor OsMYR1 can initiate symbiotic signaling as well as repress rice immunity by depleting the receptor-like kinase OsCERK1, thereby preventing the formation of the immunity complex OsCERK1-OsCEBiP in rice (Zhang et al, 2021), suggesting that OsMYR1 and OsCEBiP receptors compete to bind OsCERK1 to determine the specific response outcomes of symbiosis and immunity signals. Therefore, these lines of evidence suggest plants encountering various microbes in nature could respond appropriately to pathogenic or symbiotic microbes (Figure 2), and the exploration of plant distinguishing pathogen from rhizosphere microbiome is likely to be revealed.…”
Section: Balance Between Plant Immunity and Distinction Of Pathogens From The Rhizosphere Microbiomementioning
confidence: 99%
See 1 more Smart Citation